The hiding place - Harris, Julie, 1925-2013.; George, Jeannette Clift; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, CA : 20th Century Fox Home Entertainment, 2006)
With the Nazi invasion of Holland, Corrie ten Boom's family joins the resistance to help save persecuted Jewish families. When they are arrested and imprisoned in concentration camps themselves, they have nothing left to cling to but their faith.
DVD, region 1, widescreen presentation; Dolby Digital.
Closed-captioned.
Title from container.
Julie Harris, Jeannette Clift.
Not rated.
Director of photography, Michael Reed; music, Tedd Smith; editor, Ann Chegwidden.
Keywords: World War, 1939-1945 -- Jews -- Rescue -- Netherlands -- Drama; World War, 1939-1945 -- Concentration camps -- Drama; World War, 1939-1945 -- Jews -- Rescue -- Netherlands -- Drama; World War, 1939-1945 -- Concentration camps -- Drama; Video recordings for hard of hearing people; Feature films; Religious films; Melodrama